Equine limb cellulitis/lymphangitis resulting in distal limb ischaemia and avulsion of the hoof capsule. (30th September 2021) - Duggan, M.; Mair, T.; Fews, D.
Summary: Limb cellulitis/lymphangitis is a well‐recognised syndrome in horses, but there are limited published reports concerning outcomes and complications. This report describes a horse with hindlimb cellulitis/lymphangitis that developed ischaemia of the distal limb resulting in necrosis of the suspensory ligament branches and avulsion of the hoof capsule. A 16‐year‐old Thoroughbred mare was referred for further investigation and treatment of a left hindlimb cellulitis/lymphangitis. The culture of a swab taken from superficial pustules on the leg yielded a moderate growth of coliform bacteria and a profuse growth of Staphylococcus aureus . Treatment included systemic antimicrobials (based on the results of culture and sensitivity), phenylbutazone, dexamethasone, morphine and paracetamol. Following some initial clinical improvement, hyperextension of the metatarsophalangeal joint was noted on Day 5 of hospitalisation. Complete avulsion of the ipsilateral hoof capsule occurred on Day 10, and the horse was immediately euthanised. A limited post‐mortem examination revealed necrosis of the suspensory ligament branches. Fibrin thrombi, interstitial haemorrhage and oedema were identified in the suspensory ligament branches and adjacent subcutaneous tissues, with thrombi in relatively large vessels. The dermal laminae were extensively necrotic, and the majority of the lamellar vasculature contained fibrin thrombi.